Evaluation of Sorghum [Sorghum bicolor (L.)] Reference Genes in Various Tissues and under Abiotic Stress Conditions for Quantitative Real-Time PCR Data Normalization - Sudhakar Reddy, Palakolanu; Srinivas Reddy, Dumbala; Sivasakthi, Kaliamoorthy; Bhatnagar-Mathur, Pooja; Vadez, Vincent; Sharma, Kiran K. (Frontiers in Plant Science, 2016)
Accurate and reliable gene expression data from qPCR depends on stable reference gene expression for potential gene functional analyses. In this study, 15 reference genes were selected and analyzed in various sample sets including abiotic stress treatments (salt, cold, water stress, heat and abscisic acid) and tissues (leaves, roots, seedlings, panicle and mature green seeds). Statistical tools, including geNorm, NormFinder and RefFinder, were utilized to assess the suitability of reference genes based on their stability rankings for various sample groups. For abiotic stress, PP2A and CYP were identified as the most stable genes. In contrast, EIF4α was the most stable in the tissue sample set, followed by PP2A;PP2A was the most stable in all the sample set, followed by EIF4α. GAPDH and UBC1 were the least stably expressed in the tissue and all the sample sets. These results also indicated that the use of two candidate reference genes would be sufficient for the optimization of normalization studies. To further verify the suitability of these genes for use as reference genes, SbHSF5 and SbHSF13 gene expression levels were normalized using the most and least stable sorghum reference genes in root and water stressed-leaf tissues of five sorghum varieties. This is the first systematic study of the selection of the most stable reference genes for qPCR-related assays in Sorghum bicolor that will potentially benefit future gene expression studies in sorghum and other closely related species.